(untitled) (Raparin Journal of Humanities (RJH), 2025)
The aim of this study is to understand the effects of political discourse that electronic journalism has on voter in the Kurdistan Region. The descriptive approach was followed in this study, and the survey tool was used for a random sample of voters in the Kurdistan Region, numbering (688) people, relying on an electronic questionnaire tool that was formulated through Google Form. A non-random, intentional sample of election office officials from six major political parties in the Kurdistan Region participating in the elections was also used through scientific interviews. The study reached a number of conclusions, including: A large percentage of the study sample reads news via the Internet. The percentage of reading political discourse or political discussions by the study sample is average, while the percentage of reading political discourse through electronic journalism is low. The study sample is interested in the media content of political discourse on electronic journalism in general and video clips in particular. The study sample’s trust in the political discourse of the electronic press is satisfactory, and the percentage of criticism directed by the study sample towards the political discourse of electronic press is high. The political discourses published in electronic journalism had a moderate influence on study samples’ voting decisions for candidates or party lists .Finally, the study found that political discourse published in electronic journalism had a moderate effect on participants’ engagement in election campaigns.